Parkinson's Impulse‐Control Scale for the Severity Rating of Impulse‐Control Behaviors in Parkinson's Disease: A Semistructured Clinical Assessment Tool. Issue 5 (25th January 2016) - Okai, David; Askey‐Jones, Sally; Mack, Joel; Martin, Anne; Chaudhuri, Kallol Ray; Samuel, Michael; David, Anthony S.; Brown, Richard G.
Abstract: Background: Impulse‐control behaviors (ICBs) are increasingly recognized in Parkinson's disease (PD) as drug‐related effects of dopaminergic mediation that occur in 15% to 35% of patients with PD. The authors describe the design and evaluation of a new, clinician‐rated severity scale for the assessment of syndromal and subsyndromal forms of impulse‐control disorders (ICDs), simple (punding) and complex (hobbyism) repetitive behaviors, and compulsive overuse of medication (dopamine dysregulation syndrome). Methods: The Parkinson's Impulse‐Control Scale (PICS), the first PD‐specific, semistructured interview to cover the full range of PD‐related ICBs, is described along with initial evidence on its clinimetric properties including interrater reliability, discriminant validity and sensitivity to change. A convenience sample of PD patients with ICBs and those without were administered a semistructured interview (n = 92). Results: The scale distinguished between those with and without clinically detected ICBs and between patients with syndromal ICD and subsyndromal ICB (receiver operating characteristic areas under the curve, 92%–95%). Cutoff values were suggested, and substantial agreement was reported on weighted kappa (Κ) values for clinician‐clinician rating of severity (Κ = 0.92). Significant improvements were detected on the scale after a randomized controlled trial of cognitive‐behavioral therapy and medication adjustment ( t [22] = 5.47; P < 0.001). Conclusions: The PICS appears to be a reliable measure of the full range of PD ICBs with good levels of interrater reliability. It may provide a useful measure to assess the severity of ICBs and monitor change in clinical and research settings; although, given the specialized centers used for recruitment of this sample, further psychometric evaluation is required.